Kajian tentang faktor-faktor yang mempengaruhi tingkahlaku keselamatan dalam kalangan pekerja di UNIKL MIAT - Azizihadi, Yaakop (2018)
This study is a quantitative study that measures the safety factors among UniKL's MIA T staff against safety behavior. This study has measured safety factors such as job safety, coworker safety, supervisor safety, management safety and safety program as a independent variable (IV) affecting safety behavior (DV) as dependent variable among UniKL MIAT employees. The study also defines descriptive stage of these factors and the significant relationship between IV and DV. The findings show that there is no significant relationship between colleague safety (r == 0.070, p == 0.588) and safety program (r == -0.075, p == 0.565), while there is a significant correlation between job safety (r == 0.344, p == 0.006) supervisor safety (r == 0.3f 4, p == 0.02) and management safety (r == 0.445, p == 0.000) respectively with safety behavior. This study also shows that there is a job safety effect (B == -0.731, p == 0.000), coworker safety (B == -1.652, p == 0.000), supervisor safety (B == 1.415, p == 0.000) == -0.13, p == 0.043) with regards to safety behavior. Meanwhile, management safety (B -0.079, p == 0.636) has no influence on security behavior.